2006
DOI: 10.1080/03079450600597998
|View full text |Cite
|
Sign up to set email alerts
|

Defining susceptibility of broiler chicks to colibacillosis

Abstract: This study aimed to define the susceptibility of broilers to colibacillosis through quantification of clinical responses and to examine the relationship between susceptibility and growth retardation. A challenge experiment was carried out twice. In each trial, 192 chicks were challenged intratracheally with Escherichia coli (E. coli) at 7 days of age and 160 chicks served as controls. Surviving chicks were euthanized at 14 or 15 days. Parameters measured were: daily mortality, lesion scores, body weight at 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
3
15
0
1
Order By: Relevance
“…An association has been found between the presence of four or more of the selected APEC VGs in all of the E. coli isolates that were cultured from organs (n = 74) of chicken with colibacillosis. Similarly, Ask et al (2006) reported a direct correlation between the colibacillosis lesions and the occurrence of similar VGs. Of the 74 E. coli isolates cultured from organs, 8% (n = 6; isolates from liver and spleen of chicken 12) were lactose negative and harboured all of the five selected VGs.…”
Section: Page | 106mentioning
confidence: 78%
See 1 more Smart Citation
“…An association has been found between the presence of four or more of the selected APEC VGs in all of the E. coli isolates that were cultured from organs (n = 74) of chicken with colibacillosis. Similarly, Ask et al (2006) reported a direct correlation between the colibacillosis lesions and the occurrence of similar VGs. Of the 74 E. coli isolates cultured from organs, 8% (n = 6; isolates from liver and spleen of chicken 12) were lactose negative and harboured all of the five selected VGs.…”
Section: Page | 106mentioning
confidence: 78%
“…experimental studies have enhanced the understanding of the APEC pathogenicity mechanisms (Antão et al, 2008;Ask et al, 2006;Musa et al, 2009). However, no single or specific set of VGs have been systematically linked with APEC pathogenicity.…”
Section: Few In Vivomentioning
confidence: 99%
“…The E. coli strain 506 (serotype O78K80) used is a flumequine-resistant and doxycycline intermediary sensitive strain isolated from an inflamed pericardium from a commercial broiler suffering from natural colibacillosis (Van Eck & Goren, 1991). Its colibacillosis inducing potency was confirmed experimentally earlier (Matthijs et al, 2003;Velkers et al, 2005;Ask et al, 2006;Dwars et al, 2009). The inocula were prepared from a deep-frozen stock culture (Á708C) of this strain.…”
Section: Fungal Immunomodulatory Proteinmentioning
confidence: 99%
“…Efficacy of treatments was evaluated based on the parameters mortality, mean body weight gain between 8 and 15 days of age, colibacillosis lesion scores and generalized colibacillosis (Velkers et al, 2005;Ask et al, 2006).…”
Section: Fungal Immunomodulatory Proteinmentioning
confidence: 99%
“…The range of the immunocompetence parameters are the minimum and maximum estimates from 5 longitudinal studies (Kaleta, 1972;Boa-Amponsem et al, 1997;Toro et al, 1997;Sahin et al, 2001;Islam et al, 2002). 2 The benchmark value of the age at challenge is set to 7 d of age because this is a common choice for challenging young chicks (Ask et al, 2006). The challenge age is varied from 0 to 42 d of age.…”
Section: Simulationsmentioning
confidence: 99%